MULTICHANNEL ANALYZER (MCA) BASED ON FLASH-ADC AND FPGA FOR GAMMA RAY DETECTOR NaI(Tl) - NGUYEN , QUOC HUNG; BUI , TUAN KHAI; VO , HONG HAI (Nuclear Science and Technology, 2012)
In this article, we develop a gamma spectroscopy with the uses of a NaI(Tl) scintillation detector of 3inch x 3inch, and a multichannel analyzer (MCA) which is based on a Flash Analog-to-Digital Converter (Flash-ADC) 250 MHz-8bits and an embedded Field-Programmable Gate Array (FPGA) trigger. These hardware modules of Flash-ADC and embedded-FPGA trigger were designed and supported by Laboratory Masaharu Nomachi, Osaka University, Japan. The embedded VHDL (VHSIC Hardware Description Language) code for FPGA trigger, which was first developed by Nomachi’s group, Osaka University, Japan for double beta measurement, is modified so that it works as a MCA with 4096 Digital Charge Integration (DCI) channels for gamma spectrometry NaI(Tl). A pulse generator and two standard radioisotope sources of 133Ba and 152Eu are used for evaluating the performance of the system. The development of the gamma spectroscopy NaI(Tl) will be used for gamma study in Department of Nuclear Physics, University of Science, VNU-HCMC.